Molecular phylogenetics and biogeography of the Rhinella granulosa group : genetic divergence due to andean uplift (2017)
"The Rhinella granulosa group consists of 13 species of toad that are distributed in open areas from Argentina to Panama. The phylogenetic relationships among the species of this group have been conflictive and poorly supported under Parsimony and Bayesian inference. This study aimed to evaluate a recently published phylogeny of the group by including novel samples from the species Rhinella humboldti, from Colombia. Moreover, we estimated when and how the species of the Rhinella granulosa group split, what was the role of the Andes in the diversification, and what were the ancestral areas. Four nuclear and two mitochondrial genes were sequenced, and Bayesian inference was used to determine divergence times between clades. Our tree was very similar to the previous phylogeny; and conflictive relationships remain among R. bernardoi, R. major, R. fernandezae, R. bergi, R. pygmaea and R. azarai." -- Tomado del Formato de Documento de Grado.